Dendrimers - reflections on host-guest interaction mechanism towards solubility enhancement - Jain, Narendra K; Prajapati, Ram N; Agarwal, Abhinav; Gupta, Umesh; Asthana, Abhay (Asian Journal of Pharmaceutics (AJP), 2014)
Hydrophobicity of a bioactive is one area of major concern that poses as a great hindrance in the development of a therapeutically effective dosage form and prevents sufficient delivery of the drug to the target site. Since the last decade, dendrimers have emerged as highly promising drug delivery modules because of their unique structure and properties. Solubility enhancement is an important aspect of dendrimers and this is a synergy with site-specific drug delivery. The hydrophobic guests when entrapped in the hydrophobic channels of dendrimers are solubilized in the aqueous solution. The present article explores the various complex interaction mechanisms between the dendrimer and a bioactive. Hence the objective of this review is to reflect the host-guest interactions with the potential role of the proposed system, to enhance drug solubility and bioavailability.